High frequency ultrasonic-assisted CO2 absorption in a high pressure water batch system - Tay, W.H. (Elsevier B.V., 2016)
Physical absorption process is always nullified by the presence of cavitation under low frequency ultrasonic irradiation. In the present study, high frequency ultrasonic of 1.7 MHz was used for the physical absorption of CO2 in a water batch system under elevated pressure. The parameters including ultrasonic power and initial feed pressure for the system have been varied from 0 to 18 W and 6 to 41 bar, respectively. The mass transfer coefficient has been determined via the dynamic pressure-step method. Besides, the actual ultrasonic power that transmitted to the liquid was measured based on calorimetric method prior to the absorption study. Subsequently, desorption study was conducted as a comparison with the absorption process. The mechanism for the ultrasonic assisted absorption has also been discussed. Based on the results, the mass transfer coefficient has increased with the increasing of ultrasonic power. It means that, the presence of streaming effect and the formation of liquid fountain is more favorable under high frequency ultrasonic irradiation for the absorption process. Therefore, high frequency ultrasonic irradiation is suggested to be one of the potential alternatives for the gas separation process with its promising absorption enhancement and compact design. Â© 2016 Elsevier B.V. All rights reserved.